Phosphogypsum-waste concrete composite cementitious material for roads and preparation method thereof
By using phosphogypsum and waste concrete recycled powder, combined with microbial treatment and fluidized reactor technology, a composite gelling material with high activity and high strength was prepared, which solved the problems of insufficient material activity and environmental pollution in the prior art, and achieved efficient and environmentally friendly preparation of road base material.
Patent Information
- Application Number
- CN202411364138.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-09-28
AI Technical Summary
The prior art has problems in the preparation of road base materials with high alkali stimulator costs, large energy consumption, weak gelling material activity, low mechanical strength and not suitable for environments with large temperature differences. At the same time, the large accumulation of phosphogypsum and waste concrete leads to environmental pollution.
Phosphogypsum and waste concrete recycled powder are used as the main raw materials, and the microporous structure and surface activity of the aggregate are optimized through specific microbiome treatment and fluidization reactor technology, and modified with nano-silica dispersion to prepare a composite gelling material with high activity and high strength.
It significantly improves the gelling ability and mechanical properties of the material, enhances compressive strength, flexural strength and durability, adapts to the environment of high stress and temperature difference, reduces production costs and energy consumption, and realizes efficient resource utilization of phosphogypsum and waste concrete.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resource application of stone processing waste, and in particular to a phosphogypsum-waste concrete composite cementitious material for roads and a preparation method thereof. Background Art
[0002] Cement-stabilized gravel layer is the full name of the water-stabilized layer, which is made of cement-consolidated graded gravel, compacted and maintained. As a structural layer, the water-stabilized layer is usually used for the pavement base and subbase between the surface layer and the roadbed. Its main function is to bear loads, disperse stress, and improve its hydrological conditions. Its quality can greatly affect the performance and life of the road. The traditional method of preparing road base materials mainly uses natural resources such as lime soil, cement and gravel. Therefore, the commonly used materials for the base materials of my country's highways are fly ash stabilized gravel or cement stabilized gravel materials. This material is not only a large waste of existing natural resources, but also has an adverse impact on the surrounding environment and is costly. Therefore, it is urgent to seek other low-cost materials to replace cement for roadbed materials.
[0003] From the perspective of energy conservation, environmental protection and cost saving, the use of solid waste to prepare gel materials instead of cement has become the main research direction. This not only helps to achieve the comprehensive utilization of industrial waste and promote energy conservation and emission reduction, but also reduces corporate costs. For example, the invention patent CN113354312A discloses a method for preparing active gelling materials using industrial waste slag and the prepared active gelling materials. The active gelling materials are prepared using calcium-containing, silicon-containing waste slag and reaction accelerators as the main raw materials, and the active gelling materials are prepared through hydrothermal reaction and low-temperature activation process. The invention patent CN114477804A discloses a method for synergistically preparing high-activity gelling material raw materials with coal gangue and red mud, and high-activity gelling material raw materials and their applications. After the coal gangue and red mud are mixed evenly, they are roasted to obtain a high-activity gelling material raw material. Invention patent CN113354314B discloses a high-activity cementitious material based on construction slag, whose raw materials include the following components, and the mass percentages of each component are: 70-80 parts of construction slag, 5-10 parts of siliceous tailings, 5-10 parts of fly ash, and 10-15 parts of kiln dust; it is prepared by the following method: (1) mixing and grinding construction slag, siliceous tailings and fly ash to obtain a mixed powder; (2) placing the mixed powder and kiln dust into a calcining container, and calcining them at 700-800°C in a calcining kiln for 2-3 hours; (3) grinding the calcined product into powder to obtain a high-activity cementitious material. It can be seen that the existing cementitious materials all activate the gelling properties of waste slag through alkali activators or high-temperature thermal stimulation, but the above methods all have the problems of high cost of alkali activators, high calcination temperatures, and high energy consumption. The gelling activity of the obtained materials is weak, and they perform poorly in high-stress environments and have low toughness. In addition, the influence of ambient temperature differences on them is not considered, resulting in poor stability in low-temperature environments.
[0004] Phosphogypsum is a solid waste residue discharged from the industrial production of phosphoric acid or phosphate fertilizer. my country is the world's largest producer of phosphate fertilizer. With the rapid development of the phosphate fertilizer industry, the emission of phosphogypsum has also shown an increasing trend year by year. So far, the stockpile of phosphogypsum in my country has exceeded 300 million tons, and the annual production will exceed 70 million tons. Existing research has proved that phosphogypsum can be used as a soil conditioner, building gypsum, and road filler, but the comprehensive utilization rate of phosphogypsum is still less than 40%. With the continuous development of the urban construction industry, the consumption of concrete materials is increasing. Every year, a huge amount of waste concrete is demolished, waste concrete generated by new buildings, and waste concrete discharged by concrete plants and prefabricated component plants. After the waste concrete is crushed and screened, generally only useful recycled coarse aggregate and recycled fine aggregate are collected for the production and preparation of recycled concrete. The chemical components of waste concrete recycled powder are mainly CaO, SiO 2 and CaCO 3 Mainly, due to its low activity and low strength, it is not easy to promote and apply, and it is often discarded without being used. Phosphogypsum and waste concrete recycled powder are often treated in the form of open-air storage, which not only affects the surrounding environment, but also causes extremely serious pollution to groundwater resources. In today's world of population expansion, relative shortage of resources, and increasingly deteriorating production environment, the rational use of waste has become one of the key factors in improving the human living environment and ensuring sustainable social and economic development. Therefore, it is very necessary to speed up the research and development of new uses for phosphogypsum and waste concrete recycled powder, so as to effectively increase the utilization of phosphogypsum and waste concrete recycled powder waste and turn them into treasure. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a phosphogypsum-waste concrete composite cementitious material for roads and a preparation method thereof, so as to solve the problems of the prior art, such as high cost of alkali activators, high energy consumption, weak activity of cementitious materials, low mechanical strength and unsuitability for environments with large temperature differences, environmental pollution caused by large accumulation of phosphogypsum and waste concrete, and low degree of utilization of high value-added resources.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solution: a method for preparing a phosphogypsum-waste concrete composite cementitious material for roads, comprising the following steps:
[0007] S1: The cleaned waste concrete recycled powder and phosphogypsum are dried until the moisture content drops below 1%, and then crushed and sieved to a particle size of less than 0.6 mm to obtain fine powder; in this way, the particle grading of the system is optimized, making the powder closer to the most densely packed form, making it more conducive to filling the gaps between the slurry hardening body, and more suitable for subsequent reaction treatment.
[0008] S2: placing the microorganism in a liquid medium containing the micropowder of step S1 for continuous cultivation for 3-5 days, then filtering to obtain aggregate and drying, wherein the microorganism is composed of Bacillus, Thiobacillus and Desulfovibrio; in this way, Bacillus produces ammonia and carbonate ions during the metabolism of the liquid medium (urea), and the produced carbonate ions can combine with calcium ions in the micropowder to form calcium carbonate deposits. Thiobacillus can decompose phosphogypsum into sulfuric acid and calcium oxide through metabolism, and the decomposed sulfuric acid is then converted into hydrogen sulfide gas through the action of Desulfovibrio. On the one hand, the generated calcium carbonate and calcium oxide can increase the activity of the cementitious material, and on the other hand, the presence of alkali can effectively destroy the crystal structure of phosphogypsum. In this way, ion exchange can occur between the calcium ions in the phosphogypsum and other minerals (such as silicates) in the concrete recycled powder. This reaction promotes the release of active ingredients and further improves the gelling property of the material; and it can also promote the dissolution of active silicon and aluminum, resulting in the stimulation of the generation of hydration products with an enhancing effect, thereby enhancing the potential activity of the phosphogypsum. During the hydration, most of the micro-powders composed of phosphogypsum and waste concrete recycled powder do not participate in the hydration reaction of the cementitious material. These fine particles can be evenly dispersed in the internal structure of other road materials and filled in the gaps between the slurry hardened bodies, which can increase the density of the cementitious material and thus increase its mechanical strength. In addition, the gel produced by hydration can cover a small amount of soluble phosphorus and other impurities in the phosphogypsum, reducing its erosion effect on the cementitious material, which in turn can enhance the mechanical strength and impermeability of the cementitious material, and enhance the mechanical properties and durability of the final product.
[0009] S3: Put the aggregate obtained in step S2 into a fluidized reactor, and adjust the speed under high temperature conditions to suspend the aggregate in the bed and enter a fluidized state. After the fluidized treatment is completed, gradually reduce the air flow temperature at a rate of 20-30 minutes to 20-50°C, so that the aggregate is cooled in a suspended state; a fluidized reactor is a device that uses airflow to perform surface treatment on granular materials. By controlling the speed, temperature and composition of the airflow and the bed, uniform shaping, surface polishing and chemical modification of aggregate particles can be achieved.
[0010] S4: Placing the treated aggregate in a nano-silicon dioxide dispersion and reacting fully to obtain the composite cementitious material. In this way, the nano-silicon dioxide particles can penetrate into the tiny cracks and pores on the surface of the aggregate to form a dense nano-level protective layer, which greatly improves the toughness, compressive strength and wear resistance of the aggregate, and also improves its durability in a high stress environment.
[0011] Preferably, the mass ratio of Bacillus, Thiobacillus and Desulfovibrio in step S2 is 4-8:2-4:1-2.
[0012] Preferably, the culture conditions in step S2 are: the temperature is 30-37° C. and continuous oxygen supply is required.
[0013] Preferably, the liquid medium in step S2 comprises the following components in parts by weight: 2 to 4 parts of glucose, 1 to 2 parts of trypsin, 0.5 parts of sodium phosphate and 0.5 parts of urea, and the pH value is 6.5 to 7.5.
[0014] Preferably, the concentration of the microorganisms in the mixed solution in step S2 is 10 6 ~10 9 cells / mL; the mass volume ratio of the micropowder to the liquid medium is 0.2~1.0 g:1ml.
[0015] Preferably, the temperature of the fluidized bed treatment in step S3 is 600-800° C., and the treatment time is 40-60 min.
[0016] Preferably, the mass fraction of the nano-silicon dioxide dispersion is 4-7%.
[0017] Preferably, the reaction time in step S4 is 1 to 2 hours.
[0018] Another object of the present invention is to provide a cement-stabilized gelling material prepared by the above method.
[0019] Another object of the present invention is to provide application of the above foamed ceramic material in the preparation of road materials.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention uses waste concrete recycled powder and phosphogypsum in combination, first combines with specific microbial groups for treatment, optimizes the microscopic pore structure of aggregate, significantly improves the interface bonding performance between aggregate and cementitious materials, and more importantly, improves the cementing ability of the material, so that the activity and reactivity of this recycled material in the hardening process are significantly enhanced; then the aggregate is suspended by airflow and the surface of the aggregate is carefully treated at high temperature in combination with a silica modifier to further enhance its surface activity and mechanical strength. The present invention uses multi-level process synergy to significantly change the particle morphology, chemical activity and structural characteristics of the micropowder. The micropowder particles are more uniform, the surface is smooth, the density is increased, the porosity is reduced, the microstructure is more compact, and the impurities are reduced; the potential volcanic ash activity inside is stimulated, the chemical activity is significantly improved, and it can better participate in the hydration reaction. At the same time, the cementitious material of the present invention performs well in the mechanical properties and durability of the reinforced material, and shows better bonding ability, forming a more stable and firm combination with other road construction materials, thereby improving the overall stability and service life of the road, and has great potential and advantages to completely replace cement in road engineering.
[0022] 2. The cementitious material prepared by the present invention uses waste concrete recycled powder and phosphogypsum as the main raw materials. The raw materials are simple and easy to obtain. Not only does it not require the consumption of natural resources, but it can also improve the resource utilization rate of waste, and can also significantly reduce production costs and energy consumption. It provides a new solution for industrial solid waste, realizes the reduction and resource application of phosphogypsum and waste concrete recycled powder, and has good application prospects. At the same time, it also reduces dependence on natural resources, effectively reduces resource waste and environmental pollution, conforms to the concept of circular economy and sustainable development, promotes the construction of resource-saving and environmentally friendly industries, and realizes the strategy of sustainable development of transportation. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with examples. It should be understood that the following examples are only exemplary descriptions and explanations of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by known methods.
[0024] Example 1: A method for preparing a composite cementitious material of phosphogypsum-waste concrete for roads, comprising the following steps:
[0025] (1) The cleaned waste concrete recycled powder and phosphogypsum are placed in a drying equipment in a mass ratio of 3:1 for drying until the moisture content drops below 1%, and then further crushed and sieved to crush the crushed waste concrete to a particle size of less than 0.6 mm to obtain fine powder.
[0026] (2) Take the following microorganisms by weight: 6 parts of Bacillus, 3 parts of Thiobacillus and 2 parts of Desulfovibrio, and then culture the above microorganisms in a liquid culture medium containing the powder of step 1) (including the following components by weight: 3 parts of glucose, 2 parts of tryptone, 0.5 parts of sodium phosphate and 0.5 parts of urea, pH value is 6.5-7.5) to make the concentration of the microorganisms 10 8 cells / mL, the mass volume ratio of micropowder to liquid medium was 0.7 g:1mL, and after 4 days of continuous cultivation, the aggregates were filtered and dried.
[0027] (3) The aggregate obtained in step 2) is placed in a fluidized reactor and the temperature is set to 700°C. The air flow rate is adjusted to suspend the aggregate in the bed and enter a fluidized state. The fluidized treatment is performed for 50 minutes. After the fluidized treatment is completed, the air flow temperature is gradually reduced at a rate of 25°C per 25 minutes to cool the aggregate in a suspended state.
[0028] (4) The treated aggregate is placed in a 5% nano-silicon dioxide dispersion and reacted for 2 hours before being taken out to obtain the composite gel material.
[0029] Embodiment 2: The preparation method of the composite cementitious material of phosphogypsum-waste concrete for roads adopts the following steps:
[0030] (1) The cleaned waste concrete recycled powder and phosphogypsum are placed in a drying equipment in a mass ratio of 3:1 for drying until the moisture content drops below 1%, and then further crushed and sieved to crush the crushed waste concrete to a particle size of less than 0.6 mm to obtain fine powder.
[0031] (2) Take the following microorganisms by weight: 4 parts of Bacillus, 3 parts of Thiobacillus and 2 parts of Desulfovibrio. Then culture the above microorganisms in a liquid culture medium containing the powder of step 1) (including the following components by weight: 3 parts of glucose, 2 parts of tryptone, 0.5 parts of sodium phosphate and 0.5 parts of urea, with a pH value of 6.5-7.5) to make the concentration of the microorganisms 10 6 cells / mL, the mass volume ratio of micropowder to liquid medium was 0.4 g:1mL. After 4 days of continuous cultivation, the aggregates were filtered and dried.
[0032] (3) The aggregate obtained in step 2) is placed in a fluidized reactor and the temperature is set to 700°C. The air flow rate is adjusted to suspend the aggregate in the bed and enter a fluidized state. The fluidized treatment is performed for 50 minutes. After the fluidized treatment is completed, the air flow temperature is gradually reduced at a rate of 25°C per 25 minutes to cool the aggregate in a suspended state.
[0033] (4) The treated aggregate is placed in a 5% nano-silicon dioxide dispersion and reacted for 2 hours before being taken out to obtain the composite gel material.
[0034] Embodiment 3: The preparation method of the composite cementitious material of phosphogypsum-waste concrete for roads adopts the following steps:
[0035] (1) The cleaned waste concrete recycled powder and phosphogypsum are placed in a drying equipment in a mass ratio of 4:1 for drying until the moisture content drops below 1%, and then further crushed and sieved to crush the crushed waste concrete to a particle size of less than 0.6 mm to obtain fine powder.
[0036] (2) Take the following microorganisms by weight: 6 parts of Bacillus, 3 parts of Thiobacillus and 2 parts of Desulfovibrio. Then culture the above microorganisms in a liquid culture medium containing the powder of step 1) (including the following components by weight: 3 parts of glucose, 2 parts of tryptone, 0.5 parts of sodium phosphate and 0.5 parts of urea, with a pH value of 6.5-7.5) to make the concentration of the microorganisms 10 7 cells / mL, and the mass volume ratio of micropowder to liquid medium was 0.5 g:1 mL. After 4 days of continuous cultivation, the aggregates were filtered and dried.
[0037] (3) The aggregate obtained in step 2) is placed in a fluidized reactor and the temperature is set to 600°C. The air flow rate is adjusted to suspend the aggregate in the bed and enter a fluidized state. The fluidized treatment is performed for 50 minutes. After the fluidized treatment is completed, the air flow temperature is gradually reduced at a rate of 25°C per 25 minutes to cool the aggregate in a suspended state.
[0038] (4) The treated aggregate is placed in a 5% nano-silicon dioxide dispersion and reacted for 2 hours before being taken out to obtain the composite gel material.
[0039] Embodiment 4: The preparation method of the composite cementitious material of phosphogypsum-waste concrete for roads adopts the following steps:
[0040] (1) The cleaned waste concrete recycled powder and phosphogypsum are placed in a drying equipment in a mass ratio of 4:1 for drying until the moisture content drops below 1%, and then further crushed and sieved to crush the crushed waste concrete to a particle size of less than 0.6 mm to obtain fine powder.
[0041] (2) Take the following microorganisms by weight: 6 parts of Bacillus, 3 parts of Thiobacillus and 2 parts of Desulfovibrio, and then culture the above microorganisms in a liquid culture medium containing the powder of step 1) (including the following components by weight: 3 parts of glucose, 2 parts of tryptone, 0.5 parts of sodium phosphate and 0.5 parts of urea, pH value is 6.5-7.5) to make the concentration of the microorganisms 107 cells / mL, and the mass volume ratio of micropowder to liquid medium was 0.4 g:1 mL. After 4 days of continuous cultivation, the aggregates were filtered and dried.
[0042] (3) The aggregate obtained in step 2) is placed in a fluidized reactor and the temperature is set to 700°C. The air flow rate is adjusted to suspend the aggregate in the bed and enter a fluidized state. The fluidized treatment is performed for 50 minutes. After the fluidized treatment is completed, the air flow temperature is gradually reduced at a rate of 40°C per 30 minutes to cool the aggregate in a suspended state.
[0043] (4) The treated aggregate is placed in a 5% nano-silicon dioxide dispersion and reacted for 2 hours before being taken out to obtain the composite gel material.
[0044] Comparative Example 1
[0045] The waste concrete and phosphogypsum were crushed to a particle size of about 1.18 mm, and the other steps were the same as in Example 1.
[0046] Comparative Example 2
[0047] No Bacillus was used, and the other steps were the same as in Example 1.
[0048] Comparative Example 3
[0049] The air flow temperature is 400° C., and the other steps are the same as in Example 1.
[0050] Comparative Example 4
[0051] Cement is used as the cementitious material.
[0052] 2. Performance Verification
[0053] 1. The morphology of the composite cementitious material prepared in Example 1 was observed. The results showed that compared with the untreated material, the particles of the cementitious material prepared after treatment were more uniform, the surface was smoother, the density was increased, the porosity was reduced, and the structure was denser.
[0054] 2. Referring to the "Test Method for Cement Mortar Strength (ISO Method)" (GBT 17671-2021), the composite cementitious materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were respectively prepared into mortar test blocks according to the standard mortar strength test, and placed in a standard constant temperature and humidity curing box for curing for 28 days, and then the compressive strength, flexural strength and 25 freeze-thaw strength loss rate were tested. The results are shown in Table 1.
[0055] Table 1
[0056] performance Compressive strength of pure slurry at 28 days (MPa) 28d flexural strength of pure pulp (MPa) 25 freeze-thaw strength loss rate (%) Example 1 25.4 7.8 2.5% Example 2 21.6 6.9 2.9% Example 3 22.3 7.1 2.4% Example 4 20.5 6.3 3.1% Comparative Example 1 18.9 4.5 5.9% Comparative Example 2 15.6 4.4 5.7% Comparative Example 3 15.1 3.7 7.3% Comparative Example 4 16.4 3.9 6.8%
[0057] As can be seen from Table 1, compared with the comparative example, the mechanical properties of the cementitious material prepared by the present invention are significantly enhanced, wherein the compressive strength after curing for 28 days reaches 25.4MPa, the flexural strength can reach 7.8MPa, and the strength loss rate after 25 freeze-thaw cycles is only 2.5%, indicating that the chemical activity of the cementitious material prepared by the present invention is significantly improved, and it can better participate in the hydration reaction, while also improving the density of the structure, and enhancing the mechanical properties and durability of the material. It also has good stability at low temperatures, can adapt to large temperature differences, and improves its overall working performance as a cement stabilized cementitious material.
[0058] 3. Take 5 parts of the composite cementitious material prepared in Examples 1 to 4 or Comparative Examples 1 to 4, 40 parts of large crushed stone, 25 parts of small crushed stone and 35 parts of stone chips respectively, and prepare a mixture according to the standard "Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering" (JTG 3441-2024), and place it in a standard constant temperature and humidity curing box for 28 days, and then carry out the unlimited compressive strength test, splitting tensile strength test and freeze-thaw cycle test of the stabilized crushed stone. The experimental results are shown in Table 2.
[0059] Table 2
[0060] performance 28d unlimited compressive strength (MPa) 28d splitting tensile strength (MPa) 25 freeze-thaw strength loss rate (%) Example 1 3.4 0.31 5.2% Example 2 3.2 0.3 5.1% Example 3 3.3 0.3 6.2% Example 4 2.9 0.28 5.9% Comparative Example 1 2.5 0.19 8.9% Comparative Example 2 1.9 0.2 8.5% Comparative Example 3 2.2 0.24 8.2% Comparative Example 4 2.4 0.23 7.9%
[0061] As can be seen from Table 2, the compressive strength and tensile strength of the mixture prepared by the composite cementitious material of the present invention are better than those of the mixture prepared by cement (Comparative Example 4), showing better bonding ability, and forming a more stable and firm combination with other road construction materials, thereby improving the overall stability and service life of the road structure, and being able to meet the requirements of road construction. Therefore, the composite cementitious material of the present invention can completely replace cement for road construction, and at the same time achieves the reduction and resource application of phosphogypsum and waste concrete recycled powder.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite cementitious material of phosphogypsum-waste concrete for roads, characterized in that: The following steps are involved: S1: The cleaned waste concrete recycled powder is mixed with phosphogypsum in a mass ratio of 3-4:1 and dried until the moisture content drops below 1%, and then crushed and sieved to a particle size of less than 0.6 mm to obtain fine powder; S2: placing a microbial community in a liquid medium containing the micropowder of step S1 to obtain a mixed solution, continuing to culture for 3-5 days, then filtering to obtain aggregate and drying it, wherein the microbial community consists of Bacillus, Thiobacillus and Desulfovibrio; S3: putting the aggregate obtained in step S2 into a fluidized reactor, and adjusting the air flow velocity under high temperature conditions to suspend the aggregate in the bed and enter a fluidized state. After the fluidized treatment is completed, gradually lowering the air flow temperature at a rate of 20-30 minutes to 20-50° C., so that the aggregate is cooled in a suspended state; S4: placing the treated aggregate in a nano-silicon dioxide dispersion and obtaining the composite cementitious material after sufficient reaction.
2. The method for preparing the phosphogypsum-waste concrete composite cementitious material for roads according to claim 1, characterized in that: The mass ratio of Bacillus, Thiobacillus and Desulfovibrio in step S2 is 4-8:2-4:1-2.
3. The method for preparing the phosphogypsum-waste concrete composite cementitious material for roads according to claim 1, characterized in that: The culture conditions in step S2 are: a temperature of 30-37° C. and a continuous oxygen supply.
4. The method for preparing the phosphogypsum-waste concrete composite cementitious material for roads according to claim 1, characterized in that: The liquid medium in step S2 comprises the following components in parts by weight: 2 to 4 parts of glucose, 1 to 2 parts of tryptone, 0.5 parts of sodium phosphate and 0.5 parts of urea, and the pH value is 6.5 to 7.
5.
5. The method for preparing the phosphogypsum-waste concrete composite cementitious material for roads according to claim 1, characterized in that: The concentration of the microorganisms in the mixed solution in step S2 is 10 6 ~10 9 cells / mL; the mass volume ratio of the micropowder to the liquid medium is 0.2~1.0 g:1ml.
6. The method for preparing the phosphogypsum-waste concrete composite cementitious material for roads according to claim 1, characterized in that: The temperature of the fluidized bed treatment in step S3 is 600-800° C., and the treatment time is 40-60 min.
7. The method for preparing the phosphogypsum-waste concrete composite cementitious material for roads according to claim 1, characterized in that: The mass fraction of the nano-silicon dioxide dispersion is 4-7%.
8. The method for preparing the phosphogypsum-waste concrete composite cementitious material for roads according to claim 1, characterized in that: The reaction time in step S4 is 1 to 2 hours.
9. The composite cementitious material prepared by the method according to any one of claims 1 to 8.
10. Use of the composite cementitious material according to claim 9 in the preparation of road materials.
Citation Information
Patent Citations
Method for preparing active cementing material from industrial waste residues and prepared active cementing material
CN113354312A
A highly active cementitious material based on engineering waste soil
CN113354314B
Method for preparing high-activity cementing material raw material through synergy of coal gangue and red mud, high-activity cementing material raw material and application of high-activity cementing material raw material
CN114477804A
Preparing method of cementitious material
CN106116411A
Method for preparing phosphogypsum filling body and application
CN109485367A